Synthesis of silver/copper nanoparticles and their metalmetal bonding property - Kobayashi Y.; Shirochi T.; Yasuda Y.; Morita T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present paper describes a metal-metal bonding technique using Cu nanoparticles containing Ag nanoparticles (Ag/Cu nanoparticles). The Ag/Cu nanoparticles with particle sizes of 30-85 nm and crystal sizes of 9.3 nm for Cu and 8.1 nm for Ag were produced by reducing 5.0x10-3 M Ag+ (AgClO4) and 5.0x10-3 M Cu2+ (Cu(NO3)2) simultaneously with 1.0 M hydrazine in aqueous solution containing 1.0 g/L poly(vinylpyrrolidone) as dispersing agent and 5Ч10-3 M citric acid as stabilizer at room temperature. Discs of metallic Cu or metallic Ag were successfully bonded under annealing at 400ºC and pressurizing at 1.2 MPa for 5 min in H2 gas with help of the Ag/Cu particles. The shear strengths required for separating the bonded discs were as large as 19.7 for the Cu discs and 16.0 MPa for the Ag discs.